(untitled) (Contemporary Mathematics, 2025)
In this paper, a family of Hopf algebra which is neither pointed nor semisimple is introduced. It is shown that is quasi-triangular if and only if n is even and d = 2. The indecomposable modules of are completely classified. Moreover, the decomposition formulas of tensor product of two -modules are established.